EMPLOYEE STRIKE IN THE PERSPECTIVE OF HUMAN RESOURCES AND TRANSFORMATIVE LEADERSHIP - Sonny Wijaya; Nuri Herachwati; Gebrina Ayu Pramesti (Universitas Airlangga, 2023)
One of the human resource problems in the Company is the employee strike. The strike that resulted in the layoff employees which occurred in 2017 until now in 2022 is still a polemic. The purpose of this study is to determine the suitability of strikes carried out by workers / workers and the process of layoffs by companies with the provisions regulated in the Manpower Law and for knowing the causes of strikes from the aspects of the quality of human resources and transformational leadership. This type of research is qualitative research using a literature approach. The technique for collecting study materials is to use library research techniques, case studies and prescriptive techniques of analytical methods. The results showed that strikes carried out by workers/laborers were illegal according to laws and regulations. The act of dismissal is carried out in accordance with the provisions of the legislation.